2020
DOI: 10.1002/lary.29194
|View full text |Cite
|
Sign up to set email alerts
|

Patient Reported Outcomes and Objective Swallowing Assessments in a Multidisciplinary Dysphagia Clinic

Abstract: Objectives/Hypothesis Dysphagia encompasses a complex compilation of symptoms which often differ from findings of objective swallowing evaluations. The purpose of this investigation was to compare the results of subjective dysphagia measures to objective measures of swallowing in patients evaluated in a multidisciplinary dysphagia clinic. Study Design Prospective cohort study. Methods The study cohort included all patients evaluated in the multidisciplinary dysphagia clinic over 24 months. Participants were ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…The SLP scores VFSS findings using the Modified Barium Swallow Impairment Profile (MBSImP) to evaluate the oral, pharyngeal, and esophageal phases of swallowing. 7 We do not repeat the VFSS if it has been previously done and results are sufficient to inform decision-making. VFSS images and results, referral information, and relevant patient history are then discussed by the team before seeing the patient.…”
Section: Center Structurementioning
confidence: 99%
See 1 more Smart Citation
“…The SLP scores VFSS findings using the Modified Barium Swallow Impairment Profile (MBSImP) to evaluate the oral, pharyngeal, and esophageal phases of swallowing. 7 We do not repeat the VFSS if it has been previously done and results are sufficient to inform decision-making. VFSS images and results, referral information, and relevant patient history are then discussed by the team before seeing the patient.…”
Section: Center Structurementioning
confidence: 99%
“…The SLP also scores the patient's diet level using the Functional Oral Intake Scale (FOIS) based on information gathered during the patients' history. 7 At the end of the visit, findings of diagnostic testing are reviewed, and an overall impression is shared with the patient by the multidisciplinary team. A combined plan is discussed and depending on recommendations, a follow-up visit with the appropriate provider…”
Section: Center Structurementioning
confidence: 99%
“…Another study conducted by Arrese et al [13] comparing FOIS scores to only five of the 17 MBSImP physiologic components found no significant relationships in a small, heterogeneous group of patients with head and neck cancer [13]. Dewan et al [14] studied a cohort of patients with various dysphagia-related etiologies and found patients with impaired MBSImP total scores had significantly lower FOIS scores and significantly higher EAT-10 total scores than those without impairment [14]. They concluded that, despite these relationships, patient reports alone did not offer sufficient information to adequately describe the full relationship between physiologic swallowing impairment and swallow-specific quality of life [14].…”
Section: Introductionmentioning
confidence: 98%
“…This relationship is also shown in the swallowing literature. Studies relating physiologic swallowing impairment and functional swallowing ability, as measured by the Functional Oral Intake Scale (FOIS), and swallow-specific quality of life, as measured by the Eating Assessment Tool-10 (EAT-10), report varied results [10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation